Delayed return of spontaneous circulation (the Lazarus phenomenon) after cessation of out-of-hospital cardiopulmonary resuscitation. (September 2017) - Kuisma, Markku; Salo, Ari; Puolakka, Jyrki; Nurmi, Jouni; Kirves, Hetti; Väyrynen, Taneli; Boyd, James
Abstract: Introduction: The delayed return of spontaneous circulation (ROSC) after cessation of cardiopulmonary resuscitation (CPR), also known as the Lazarus phenomenon, is a rare event described in several case reports. This study aims to determine the incidence and the time of occurrence of the Lazarus phenomenon after cessation of out-of-hospital CPR. Methods: This prospective observational cohort study was conducted in the Helsinki Emergency Medical Service in Finland from 1 January 2011 through 31 December 2016. All out-of-hospital CPR attempts were carefully monitored for 10 min after the cessation of CPR in order to detect delayed ROSC. Results: Altogether, 2102 out-of-hospital cardiac arrests occurred during the six-year study period. CPR was attempted in 1376 (65.5%) cases. In 840 cases (61.0% of all attempts) CPR attempts were terminated on site. The Lazarus phenomenon occurred five times, with an incidence of 5.95/1000 (95% CI 2.10–14.30) in field-terminated CPR attempts. Time to delayed ROSC from the cessation of CPR varied from 3 to 8 min. Three of the five patients with delayed ROSC died at the scene within 2–15 min while two died later in hospital within 1.5 and 26 h, respectively. Conclusions: We observed that the Lazarus phenomenon is a real albeit rare event and can occur a few minutes after the cessation of out-of-hospital CPR. We suggest a 10-min monitoring period before diagnosing death. CPR guidelines should be updated to include information of the Lazarus phenomenon and appropriate monitoring for it.